Penerapan Sistem ERP pada UMKM Zevenstore Di Kota Batam - Golan Hasan; Agika Wasinta Br Sembiring; Rahel Nur Hamidah; Estefania Estefania; Eva Noorliana (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2022)
This research focuses on implementing the Enterprise Resources Planning (ERP) system in Zevenstore micro, small and medium enterprises. This study aims to analyze the Enterprise Resources Planning (ERP) system in integrated business management applications used by industry to perform all its functions such as Planning, Production Management, Sales Management, Financial Management, Human Resources. descriptive. data collection method using primary data and secondary data. The result of the research is that in determining the success of ERP, there are 5 criteria in the Zevenstore ERP module selection process, the first is the criteria for adjustment to needs, technical criteria, cost and budget criteria, service and support criteria, and the last is conformity criteria.